Wine pomace seasoning attenuates hyperglycaemia-induced endothelial dysfunction and oxidative damage in endothelial cells - Raquel Del Pino-García; Gisela Gerardi; María D. Rivero-Pérez; María L. González-SanJosé; Javier García-Lomillo; Pilar Muñiz (Journal of Functional Foods, 2016)
Dietary antioxidants such as phenolic phytochemicals may prevent/improve endothelial function impairment observed in cardiovascular diseases. This study investigates the specific protective effects of a vegetal seasoning obtained from seedless wine pomace against hyperglycaemia-induced oxidative damage and dysfunction in human umbilical vein endothelial cells EA.hy926. Non-cytotoxic doses of the bioactive compounds obtained following in vitro digestion of the seasoning were used as treatments. Digested compounds, especially colonic bacterial metabolites, restored a more balanced redox environment, prevented lipid peroxidation and cell membrane damage, ameliorated protein oxidation, and improved the balance between endothelial reactive oxygen species and nitric oxide production in hyperglycaemic cells. Reduction of angiotensin I-converting enzyme activity and gene modulation of superoxide dismutase, haem oxygenase-1, β-nicotinamide adenine dinucleotide phosphate oxidase-4, and endothelial nitric oxide synthase are proposed as the mechanisms underlying this protection. These results support the potential benefits of functional wine pomace seasonings in vascular complications associated with oxidative stress.